Ostrovrhar – nov slovenski mit?Ostrovrhar – a New Slovenian Myth? - Grilc, Viktor (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article deals with the historical, literary character of Ostrovrhar as a quasi-Slovenian medieval knight in the Slovenian people’s subconscious, with recognizable elements of mythical proportions. Ostrovrhar originates in the genealogical work of Schönleben from where he was taken over by Valvasor in his monumental work “Die Ehre...” Several romantic and post-romantic Slovenian writers and poets, Prešeren being the most significant among them, transformed Ostrovrhar into a symbolic heroic figure for national awakening and liberation from historic bonds. The frequency of the appearance of the heroic Ostrovrhar in Slovenian literature has crucially determined people’s recognition and reflection. HisHis H gradual transition into other forms and social phenomena justifies the hypothesis of the mythic dimension of the contemporary perception of this person.